2015
DOI: 10.1134/s1560354715060088
|View full text |Cite
|
Sign up to set email alerts
|

On geodesics of the rotation group SO(3)

Abstract: The simplest model with which to examine the dynamics of the human eye consists of a rigid body which is free to rotate about a fixed point. Two classical laws governing monocular vision, which are known as Listing's law and Donders' law, can be enforced in this model using a single holonomic constraint. While there has been considerable attention paid to the kinematics of the eye, the dynamics of the eye predicted by rigid body models has not received the same level of attention. In the present paper, the unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For a general introduction to analysis on smooth manifolds which includes smooth coverings, see, e.g., [47]. For a dynamical systems approach to quaternions, see, e.g., [72] which nicely demonstrates the usefulness of quaternions for mechanics applications with constraints. A more algebraic approach to quaternions with historical remarks is given in [25], and, finally, for those who enjoy the classics, see [37] and [38].…”
Section: Solvable Euler-lagrange Equations: Transformation Lift and L...mentioning
confidence: 99%
See 1 more Smart Citation
“…For a general introduction to analysis on smooth manifolds which includes smooth coverings, see, e.g., [47]. For a dynamical systems approach to quaternions, see, e.g., [72] which nicely demonstrates the usefulness of quaternions for mechanics applications with constraints. A more algebraic approach to quaternions with historical remarks is given in [25], and, finally, for those who enjoy the classics, see [37] and [38].…”
Section: Solvable Euler-lagrange Equations: Transformation Lift and L...mentioning
confidence: 99%
“…For some interesting recent applications to strain measures in mechanics, see, e.g., [64]. Another interesting recent usecase for geodesics on the group of unit quaternions is the simulation of eye movements, see [72].…”
Section: Validation Of Optimality By Monte Carlo Statistical Samplingmentioning
confidence: 99%
“…where the (X I , Y I ) → T race {X I .Y I } map is called the Killing form of SO(3) [9]. Since h has nondegenerate, symmetric, bilinear form, h will be a semi-Riemann metric on SO(2, 1).…”
Section: Definition 24mentioning
confidence: 99%
“…Moreover, they described the kinetic energy of a rotating particle in terms of the unit quaternion. They showed that kinetic energy of the rotating particle is constant along the geodesics of the special orthogonal group [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation